Advances in the clinical diagnosis and treatment of multiple-level noncontiguous spinal fractures - Luo, Bangmin; Chen, Huarong; Zou, Mingxiang; Yan, Yiguo; Ouyang, Xueqian; Wang, Cheng (Frontiers in Neurology, 2024)
Multiple-level noncontiguous spinal fractures (MNSF) are spinal fractures that involve at least 2 sites and are characterized by the presence of one intact vertebra or intact functional spinal unit between the fractured vertebrae. MNSF account for 2.5–19% of all spinal fractures. MNSF are easily missed or have a delayed diagnosis in clinical practice and their treatment is more complex than that for single-segment spine fractures. In this article, the authors briefly summarize the advances in the etiology and mechanisms of MNSF, the identification of their involved sites and their classification, diagnosis, treatment, and prognosis.